Nut consumption and risk of cardiovascular disease, total cancer, all-cause and cause-specific mortality: a systematic review and dose-response meta-analysis of prospective studies - Aune,D; Keum,N; Giovannucci,E; Fadnes,LT; Boffetta,P; Greenwood,DC; Tonstad,S; Vatten,LJ; Riboli,E; Norat,T (BMC Medicine, 2016)
Background: Although nut consumption has been associated with a reduced risk of cardiovascular disease and all-cause mortality, data on less common causes of death has not been systematically assessed. Previous reviews missed several studies and additional studies have since been published. We therefore conducted a systematic review and meta-analysis of nut consumption and risk of cardiovascular disease, total cancer, and all-cause and cause-specific mortality. Methods: PubMed and Embase were searched for prospective studies of nut consumption and risk of cardiovascular disease, total cancer, and all-cause and cause-specific mortality in adult populations published up to July 19, 2016. Summary relative risks (RRs) and 95% confidence intervals (CIs) were calculated using random-effects models. The burden of mortality attributable to low nut consumption was calculated for selected regions. Results: Twenty studies (29 publications) were included in the meta-analysis. The summary RRs per 28 grams/day increase in nut intake was for coronary heart disease, 0.71 (95% CI: 0.63-0.80, I2=47%, n=11), stroke, 0.93 (95% CI: 0.83-1.05, I2=14%, n=11), cardiovascular disease, 0.79 (95% CI: 0.70-0.88, I2=60%, n=12), total cancer, 0.85 (95% CI: 0.76-0.94, I2=42%, n=8), all-cause mortality, 0.78 (95% CI: 0.72-0.84, I2=66%, n=15), and for mortality from respiratory disease, 0.48 (95% CI: 0.26-0.89, I2=61%, n=3), diabetes, 0.61 (95% CI: 0.43-0.88, I2=0%, n=4), neurodegenerative disease, 0.65 (95% CI: 0.40-1.08, I2=5.9%, n=3), infectious disease, 0.25 (95% CI: 0.07-0.85, I2=54%, n=2), and kidney disease, 0.27 (95% CI: 0.04-1.91, I2=61%, n=2). The results were similar for tree nuts and peanuts. If the associations are causal, an estimated 4.4 million premature deaths in the America, Europe, South-East Asia and Western Pacific would be attributable to a nut intake below 20 grams per day in 2013.Conclusion: Higher nut intake is associated with reduced risk of cardiovascular disease, total c